1981
DOI: 10.1007/bf01852123
|View full text |Cite
|
Sign up to set email alerts
|

Zur intestinalen Absorption von Zink während der Gravidität und Laktation

Abstract: In two experimental series the absorption of zinc was continuously studied during gravidity and lactation with Sprague-Dawley rats of the same age. The absorption was measured in vitro with isolated, everted intestinal sacs. During the first third of gravidity the absorption of zinc--based on the intestinal Zn transfer to the serosal solution and the Zn uptake into the intestinal wall--rose at first slightly, during the second third it continued to increase, whereas there was a highly significant increase duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The excess of zinc absorbed during pregnancy is stored in body pools ("Super retention") and is used for the consecutive lactation period. The rate of zinc absorbed during lactation depends on the amounts of zinc stored in the body during pregnancy (Davis and Williams 1977, Schwarz et al 1981).…”
Section: Absorption In Mammalsmentioning
confidence: 99%
“…The excess of zinc absorbed during pregnancy is stored in body pools ("Super retention") and is used for the consecutive lactation period. The rate of zinc absorbed during lactation depends on the amounts of zinc stored in the body during pregnancy (Davis and Williams 1977, Schwarz et al 1981).…”
Section: Absorption In Mammalsmentioning
confidence: 99%
“…Für Mangan steigt dabei nicht nur die ge samte Retention, sondern auch die Mn-Konzentration in der Leber und im Ganzkörper ist gegenüber den nichtgraviden Kontrollratten eindeutig erhöht [21]. Dies überrascht, da Absorptionsänderungen für Mangan auf grund einer unterschiedlichen Versorgung, des Alters oder der Trächtigkeit stets weniger deutlich ausgeprägt sind als für das Spuren element Zink [18][19][20] …”
Section: Introductionunclassified
“…Using the duodenal loop technique, it has been shown that zinc absorption increased after pregnancy termination (4), and other authors (21) also found that the zinc uptake and transfer across isolated everted intestinal sacs from pregnant rats was significantly higher than that of control animals during the last third of gestation.…”
mentioning
confidence: 99%